Comparación de la resistencia de tres sistemas cerámicos en tramos protésicos fijos anteriores. Análisis por elementos finitos (2013)
ABSTRACT: The purpose of this study was to evaluate stress distribution on three-unit fixed partial dentures (FPD) in the anterior region, made of three ceramic systems with connector variations. The study was performed by the finite element method. Methods: four segments of FPD were modeled; three of them were made on ceramic systems: lithium disilicate, alumina, and zirconia, and the fourth model was of lithium disilicate with a connector of 9 mm2 in area. The modeling included three variables: elastic modulus, Poisson’s ratio, and ultimate tensile strength. An initial load of 200 N was applied and increased up to 1000 N calculating von Mises, maximum tensile, compressive, and shear stresses. Results and conclusions: all the ceramic systems showed a suitable behavior for FPDs in the anterior area; the structure’s elastic modulus influences stress behavior; if it is higher, it reduces stresses in feldspar ceramics and periodontal ligament. We noted that in presence of a connector of 16 mm2 in area, the periodontal ligament received greater stresses as a compensation effect, but they significantly decreased in the structure. By reducing the connector area to 9 mm2, the stresses increased to 48%, but did not reach yield strength when subjected to loads of 1000 N, providing the system with proper margin tolerance without fracturing.